Induction Therapy With Antithymocyte Globulin in Patients Undergoing Cardiac Transplantation Is Associated With Decreased Coronary Plaque Progression as Assessed by Intravascular Ultrasound. (January 2016) - Azarbal, Babak; Cheng, Richard; Vanichsarn, Christopher; Patel, Jignesh K.; Czer, Lawrence S.; Chang, David H.; Kittleson, Michelle M.; Kobashigawa, Jon A.
Abstract : Background—: Antithymocyte globulin (ATG) is used as induction therapy after cardiac transplant for enhancing immunosuppression and delaying the initiation of nephrotoxic drugs. It is unknown if ATG induction is associated with decreased coronary plaque progression by intravascular ultrasound (IVUS). Methods and Results—: Patients transplanted between March 2010 and December 2012 with baseline and 1-year IVUS were included. All patients transplanted were included in a secondary analysis. Change in plaque progression was measured in a blinded fashion on matched coronary segments and contrasted between patients induced with ATG and those who were not. One hundred and three patients were included in IVUS arms. Mean age at transplant was 55.8±12.6 years, and 33.0% were female. Patients induced with ATG were more sensitized (54.3% versus 14.3%). Plaque progression was attenuated in patients who received ATG by changes in maximal intimal area (1.0±1.2 versus 2.3±2.6 mm 2 ; P =0.001), maximal percent stenosis (6.3±7.9 versus 12.8±12.3%; =0.003), maximal intimal thickness (0.2±0.2 versus 0.3±0.3 mm; P =0.035), and plaque volume (0.5±0.7 versus 1.0±1.3 mm 3 /mm; P =0.016). Rapid plaque progression by maximal percent stenosis (≥20%) occurred less frequently in the ATG arm (4.3% versus 26.3; P =0.003). Survival ( P =0.242) and any treated rejection ( P =0.166) were not statistically different between groups. Patients receiving ATG had a higher rate of first-year infection ( P =0.003), perhaps related to increased intravenous antibiotic use immediately postoperatively, and a trend toward more biopsy-proven rejection ( P =0.073). Conclusions—: Induction therapy with ATG is associated with reduced first-year coronary plaque progression as assessed by IVUS, despite an increased prevalence of sensitized patients with a trend toward more rejection.